KLASIFIKASI STRATEGI PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS DAN PENGARUHNYA TERHADAP KARAKTER SISWA - Samwil Samwil; Rita Hartati (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2020)
The learning strategy is an important thing in achieving learning objectives. This strategy is ideally chosen according to the nature or character of the subject matter itself. Islamic Religious Education is one of the compulsory subjects in senior high schools. The main objective of this subject is to equip students with Islamic values so that students have an Islamic character. Religious education has its own strategy in addition to the strategies commonly used in learning other subjects. Besides that, Islamic religious studies also have specific objectives in shaping attitudes as well as educating reason. Meanwhile, in evaluating the success of Islamic religious learning, it does not only assess cognitive abilities and psiokomor, but also emphasizes attitude assessment. This can be done through non-test techniques.